2010
DOI: 10.3945/ajcn.2010.29812
|View full text |Cite
|
Sign up to set email alerts
|

Eating in the absence of hunger in adolescents: intake after a large-array meal compared with that after a standardized meal

Abstract: Background: Eating in the absence of hunger (EAH) is typically assessed by measuring youths' intake of palatable snack foods after a standard meal designed to reduce hunger. Because energy intake required to reach satiety varies among individuals, a standard meal may not ensure the absence of hunger among participants of all weight strata. Objective: The objective of this study was to compare adolescents' EAH observed after access to a very large food array with EAH observed after a standardized meal. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 36 publications
2
87
1
1
Order By: Relevance
“…This is a relevant issue because the role of palatable food as a motivating force able to override homeostatic signals still remains controversial [41][42][43]. Indeed, a profound state of reward hyposensitivity accompanied by compulsive-like eating, as a consequence of over-stimulation of brain reward systems triggered by cafeteria diet, has been reported [44].…”
Section: Discussionmentioning
confidence: 96%
“…This is a relevant issue because the role of palatable food as a motivating force able to override homeostatic signals still remains controversial [41][42][43]. Indeed, a profound state of reward hyposensitivity accompanied by compulsive-like eating, as a consequence of over-stimulation of brain reward systems triggered by cafeteria diet, has been reported [44].…”
Section: Discussionmentioning
confidence: 96%
“…In early studies, youth with obesity ate significantly more when presented with snacks (Costanzo & Woody, 1979) and were more influenced by external cues such as the availability or composition of food (Schachter, 1971; Schachter & Rodin, 1974) than youth who were lean. More recent studies also have demonstrated a positive cross-sectional association between EAH, as assessed by survey and test meal intake, with body mass index (BMI) in adolescents (Fisher et al, 2007; Shomaker et al, 2010). …”
Section: Introductionmentioning
confidence: 97%
“…'High' versus 'low' scores were based on median splits at each age, specifically, 49 kcal (age 5 years) and 76 kcal (age 7 years) [21] . EAH was associated with a greater BMI zscore and overweight/obesity status (i.e., not overweight/ obese vs. overweight/obese) among adolescents, even when the ad libitum lunch meal preceding the free-access procedure provided multiple food options comprising more than 10,000 kcal [26] . A recent study of 5-to 9-yearold children that invoked an anticipatory laboratory 82 stressor (i.e., instructing children to deliver a speech and solve math problems) found that children consumed on average 250 kcal in the absence of hunger, with intakes ranging as high as 700 kcal [27] .…”
Section: Food Intake Self-regulation Indexesmentioning
confidence: 99%